2019
DOI: 10.1007/s10900-019-00637-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Affordable Care Act Medicaid Expansion on Type 2 Diabetes Diagnosis and Treatment: A National Survey of Physicians

Abstract: Introduction-In 2014, the Affordable Care Act (ACA) provided funding for states to expand Medicaid coverage to include citizens who earned up to 138% of the federal poverty line. We sought to ascertain whether physicians practicing in Medicaid expansion states reported an increase in Medicaid or newly insured patients with type 2 diabetes in their panels, compared to physicians practicing in non-expansion states. Methods-We conducted a 55-question cross-sectional survey of 356 physicians providing outpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We posit that improved access to healthcare insurance such as Medicaid expansion could lead to lower uninsured rates among low-income individuals, improving access to healthcare, thereby lowering the adverse impact of COVID-19 in low-income communities. 23,35,36 Limitations and Strengths This is a nationwide study, that utilized representative data of US communities suitable to assess outcomes as it relates to policy. Study limitations include its observational design, inability to conclude causality and the potential for residual confounding despite our careful control of known confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We posit that improved access to healthcare insurance such as Medicaid expansion could lead to lower uninsured rates among low-income individuals, improving access to healthcare, thereby lowering the adverse impact of COVID-19 in low-income communities. 23,35,36 Limitations and Strengths This is a nationwide study, that utilized representative data of US communities suitable to assess outcomes as it relates to policy. Study limitations include its observational design, inability to conclude causality and the potential for residual confounding despite our careful control of known confounders.…”
Section: Discussionmentioning
confidence: 99%
“…We posit that improved access to healthcare insurance such as Medicaid expansion could lead to lower uninsured rates among low-income individuals, improving access to healthcare, thereby lowering the adverse impact of COVID-19 in low-income communities. 23,35,36…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature shows that individuals without health insurance are less likely to seek health care even when in need [33]. In contrast, it has been shown that when they could afford care, individuals were more likely to utilize healthcare resources [23,[34][35][36]. Therefore, while a proportion of population in high income communities are able to afford insurance regardless of state Medicaid expansion status, exemplified by similar mortality rates between counties in the highest-income quartiles between Medicaid vs. non-Medicaid expansion states, the highest mortality rate gap is observed in the lowest-income quartiles.…”
Section: Plos Onementioning
confidence: 99%